The Lymphaticovenous Anastomosis for the Treatment of Lymphoedema - Danza, Rómulo; Baldizán, Jorge; Navarro, Teodoro; Grillo, Bartolomé (Cirugía del Uruguay, 1981)
Lymphovenous derivation is indicated in lymphoedema of limbs when this condition is accompanied by • dilation of collectors; and it is particularly useful when fibroedema has not yet set in.